Let the line (x - 2)/3 = (y - 1)/-5 = (z - 2)/2 lie in the plane x + 3y - αz + β = 0. Then (α, β) equals

- (-5, 5)
- (5, -15)
- (-6, 7)
- (6, -17)

**Answer**

2 + 3 × 1 – α (–2) + β = 0

2α + β = –5

3 – 15 – 2α = 0

2α = –12

**The correct option is C.**

Let the line (x - 2)/3 = (y - 1)/-5 = (z - 2)/2 lie in the plane x + 3y - αz + β = 0. Then (α, β) equals

- (-5, 5)
- (5, -15)
- (-6, 7)
- (6, -17)

**Answer**

2 + 3 × 1 – α (–2) + β = 0

2α + β = –5

3 – 15 – 2α = 0

2α = –12

**The correct option is C.**